Primitive Magmas in the Early Central American Volcanic Arc System Generated by Plume-Induced Subduction Initiation - Whattam, Scott A. (Frontiers in Earth Science, 2018)
Primitive lavas with Mg# ≥60 have been identified in the literature from the Sona-Azuero, Golfito and Chagres-Bayano forearc segments of southern Costa Rica and Panama of the early (75-39 Ma) Central American Volcanic Arc system (CAVAS). Primitive CAVAS basalts are remarkably similar in terms of major and many trace elements to primitive MORB and primitive basalts of the Mariana Arc. Significant differences however, are apparent between primitive lavas of Chagres-Bayano relative to those of Sona-Azuero and Golfito. Primitive Chagres-Bayano lavas record much higher degrees of partial melting and higher amounts of shallow and deep subduction additions (e.g., higher Ba/Th, Th/Nb) than those of the older Sona-Azuero and Golfito arc segments which reflects the early petrologic and tectonic evolution of the CAVAS which is similar to other forearc systems. As shown in previous studies, early CAVAS lavas are exceptionally similar in radiogenic isotopic composition to those of the Caribbean Large Igneous Province (CLIP) oceanic plateau at 90 Ma, the approximate timing of onset of the volumetrically dominant phase of CLIP magmatism. This recognition is consistent with subduction initiation models which require plume-subduction interaction. Such models also dictate that an elevated sub-arc thermal anomaly was present at inception of the CAVAS. It is postulated that in addition to providing an anomalously high temperature regime in the sub-arc mantle at inception of the CAVAS, that extrusion of the CLIP also resulted in lithospheric weakening and extension which allowed for production and rapid ascent of a high percentage of primitive lavas.